Ethanol Total Oxidation Over Calcined Layered Double Hydroxides Modified with Organic Components - Kovanda, F.; Zapivovarski Votipka, Z.; Raabová, H.; Jirátová, K.; Klempa, J.; Ludvíková, J. (Kemija u Industriji, 2013)
Coprecipitation of Co, Mn, and Al nitrates by a solution of Na2CO3 and NaOH in the presence of Pluronic ® P123 has led to layered double hydroxide (LDH) precursors with hydrotalcite-like structure. Their calcination gave spinel-type mixed oxides; the presence of organic template increased both BET and mesopore surface areas of the calcined products. TPR profiles of the samples modified with Pluronic ® P123 exhibited a shift of reduction maxima to lower temperatures, similarly as increasing sodium content in the catalysts. However, though the physical-chemical properties of Co-Mn-Al mixed oxides and their catalytic activity in ethanol oxidation were slightly improved, the changes evolved by the presence of Pluronic ® P123 during precipitation of LDH precursors were rather small.